1977
DOI: 10.1017/s002185960002832x
|View full text |Cite
|
Sign up to set email alerts
|

Fat-tailed Awassi and German Mutton Merino sheep under semi-arid conditions: 3. Body temperatures and panting rate

Abstract: Rectal, external auditory meatus and skin temperatures and panting rates were measured in native fat-tailed Awassi and imported German Mutton Merino (GMM) sheep. The Awassi evolved under desert conditions, have a localized fat deposit, coarse carpet wool, long pendulous ears and long, spiral horns (males). In contrast, the GMM evolved under temperate conditions, have well-distributed fat, medium fine wool, short, straight ears and are polled. The study was carried out during the summer in the northern part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Pregnant and lactating animals have 40-50% higher water turnover rates than dry animals [17]. However, Degen (1977) [35] recorded a small difference in water turnover between control and pregnant Awassi and Merinos sheep.…”
Section: Changes In Relation With Physiological Statusmentioning
confidence: 90%
See 2 more Smart Citations
“…Pregnant and lactating animals have 40-50% higher water turnover rates than dry animals [17]. However, Degen (1977) [35] recorded a small difference in water turnover between control and pregnant Awassi and Merinos sheep.…”
Section: Changes In Relation With Physiological Statusmentioning
confidence: 90%
“…Aspirin did not have any effect on rectal temperature; perhaps these results highlight the capacity of Awassi to remain thermostable even under dehydration [10,35]. No changes were detected in PCV and hemoglobin levels [62] confirming that salicyclates do not usually alter these two parameters [188].…”
Section: Aspirinmentioning
confidence: 97%
See 1 more Smart Citation
“…Some, like the Bedouin goats that can produce milk up to about 10% of their body weight, keep a large extracellular volume when fully hydrated. 7 The Moroccan black goat 8 and Awassi sheep, 9 on the other hand, produce small amounts of milk and have a low water turnover. Pastoralists often use intermittent watering in the desert.…”
Section: Fluid Balancementioning
confidence: 99%
“…Hyperthemia is one of mechanisms that allow animals to avoid excessive water expenditure during the hot part of the dayespecially as our study was conducted during the warmer months of the year. On the other side, authors reported that sheep are thermostable even during dehydration [14].…”
Section: Discussionmentioning
confidence: 99%